1995
DOI: 10.1044/jshr.3806.1319
|View full text |Cite
|
Sign up to set email alerts
|

Redirects: A Strategy to Increase Peer Initiations

Abstract: Preschoolers’ verbal abilities influence their verbal interactions with play partners. Previous research has suggested that preschoolers with specific language impairment (SLI) are more likely to initiate conversations with adults than with peers, as compared to their typically developing peers. This study investigated a teacher-implemented procedure, redirects, as a means to facilitate initiations to peers. A redirect occurs when a child initiates to the teacher, and the teacher then suggests the child initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 8 publications
1
26
0
6
Order By: Relevance
“…For instance, adult use of open-ended questions, repetitions, and expansions of children's utterances has been found to relate to children's performance on measures of syntax and vocabulary (Arnold, Lonigan, Whitehurst, & Epstein, 1994;Lonigan & Whitehurst, 1998;Valdez-Menchaca & Whitehurst, 1992;Whitehurst et al, 1988). Likewise, redirecting a child to initiate conversation with another peer rather than an adult has been shown to increase peer interactions for preschoolers with specific language impairment (SLI; Schuele et al, 1995), and using focused contrasts in the preschool classroom has been shown to provide measurable gains in phonology for children with SLI (Wilcox & Morris, 1995).…”
Section: Discussion Of Major Findingsmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, adult use of open-ended questions, repetitions, and expansions of children's utterances has been found to relate to children's performance on measures of syntax and vocabulary (Arnold, Lonigan, Whitehurst, & Epstein, 1994;Lonigan & Whitehurst, 1998;Valdez-Menchaca & Whitehurst, 1992;Whitehurst et al, 1988). Likewise, redirecting a child to initiate conversation with another peer rather than an adult has been shown to increase peer interactions for preschoolers with specific language impairment (SLI; Schuele et al, 1995), and using focused contrasts in the preschool classroom has been shown to provide measurable gains in phonology for children with SLI (Wilcox & Morris, 1995).…”
Section: Discussion Of Major Findingsmentioning
confidence: 96%
“…Adult use of pragmatic strategies such as waiting, turn taking, face-to-face interaction (i.e., by positioning oneself to be on the child's level), and including uninvolved children in interactions increases children's language use and participation in conversations (Girolametto et al, 2003). In addition, redirecting children's verbal initiations to peers rather than to adults increases opportunities for children to interact in peer-to-peer conversation (Schuele, Rice, & Wilcox, 1995).…”
Section: Children's Exposure To Language In the Preschool Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…Children who can successfully interact with peers are more likely to develop friendships , have better oral language skills (Mashburn, Justice, Downer, & Pianta, 2009;Schuele, Rice, & Wilcox, 1995), and have better early adjustment at school (Ladd, Kochenderfer, & Coleman, 1996). In an experimental study by Girolametto et al (2004), ECPs in the experimental group were taught to facilitate children's interactions with their peers by using direct referrals (e.g., telling a child what to say to a peer, inviting children to play together).…”
Section: Skill Area 4: Developing Peer-to-peer Interactionsmentioning
confidence: 99%
“…Studies of teacher-implemented intervention programs are very limited at this point but suggest that teachers can also be effective in facilitating children's language development and conversational behavior [56,57]. This type of research will be important given the increasing use of consultative intervention models with school-aged language-disordered children [58,59].…”
Section: Intervention Research: Intervention Agentsmentioning
confidence: 99%